2021
DOI: 10.18860/ling.v16i1.10832
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Analysis of Sentence Patterns and Types of BBC News Articles

Abstract: Sentence patterns and types play a crucial role in helping writers make their articles attractive. However, few studies analyzed the sentence patterns and types used in news articles. Therefore, this study aimed to explore the sentence patterns and types used in shaping news articles. The researchers used a syntactic analysis to examine the sentences. The data were collected from ten BBC news articles published in October 2020. The purposive sampling was used, and the data gathering instrument was structured o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The recent Indonesian study (Andriani and Bram, 2021) reviewed in this paper found only five sentence patterns in the BBC news articles studied. SVA and SVOA were not identified by the authors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The recent Indonesian study (Andriani and Bram, 2021) reviewed in this paper found only five sentence patterns in the BBC news articles studied. SVA and SVOA were not identified by the authors.…”
Section: Discussionmentioning
confidence: 96%
“…Like Quirk et al (1985), Blake (1988) mentions seven types of clause arrangements, but the only difference in the two is Blakes' P (predicate) instead of Quirk et al's V although they mean the same (SP, SPO, SPC, SPA, SPOO, SPOC, SPOA). Andriani and Bram (2021) highlighted five sentence patterns namely, SV, SVC, SVO, SVOC and SVOO, and SVO was found to be the most frequent (42%) sentence pattern used in the BBC news articles. This pattern was followed by SV, SVC, SVOC and SVOO respectively.…”
Section: Syntactic Functions Of Clause Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the previous study of this study is from Pamungkas (2020) on his thesis entitled "Syntactic Analysis on Sentence Patterns In "Bahasa Inggris" Text Book for Senior High School" Broke down the constituents of the sentence through the tree diagram. Secondly, Andriani & Bram (2021) From the two relevant previous studies above, all of them have the similar aspect to each other's researches, especially the sentence pattern. This study will be conducted by Danin (2018), specifically; Calum Scott's song lyrics were taken as the object of this study.…”
Section: Introductionmentioning
confidence: 83%
“…There is a review of several relevant previous studies to support this research. The first research was done in an article titled "Syntactic Analysis of Sentence Pattern and Types of BBC News Articles" by Andriani & Bram (2021). It concentrated on analyzing the many types and phrase patterns that are essential for assisting authors in making their writings engaging.…”
Section: Introductionmentioning
confidence: 99%